2018
DOI: 10.3390/su10061792
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Sustainability Performance of Organic and Low-Input Conventional Farms from Eastern Poland with the RISE Indicator System

Abstract: Abstract:The aim of this study was to examine the sustainability performance of organic and low-input conventional farms with the sustainability assessment tool-RISE 3.0. It is an indicator-based method for holistic assessment of sustainability of agricultural production at farm level. Ten organic and 10 conventional farms from eastern Poland, Lublin province were assessed. According to the thresholds levels of the RISE method, organic farms performed positively for 7 out of 10 themes, while the values of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 37 publications
0
12
0
1
Order By: Relevance
“…This group gathers studies where stakeholders have been consulted on selection of indicators and on the definition of the problem of sustainability. This group encompasses frequently used tools such as the RISE tool (Response-Inducing Sustainability Evaluation), which is an indicator-based tool for holistic assessment of sustainability of agricultural production at farm level (Berbeć et al 2018), or the SMART tool (Sustainability Monitoring and Assessment Routine -Farm Tool) (Schader et al 2016), which is similar to the RISE tool. These tools assess the sustainability of agricultural production at farm level using comprehensive information on ecological, economic and social aspects collected through a questionnairebased interview with the farmer (Grenz et al 2012).…”
Section: Group 4: Consultation-based Assessment (N = 26)mentioning
confidence: 99%
“…This group gathers studies where stakeholders have been consulted on selection of indicators and on the definition of the problem of sustainability. This group encompasses frequently used tools such as the RISE tool (Response-Inducing Sustainability Evaluation), which is an indicator-based tool for holistic assessment of sustainability of agricultural production at farm level (Berbeć et al 2018), or the SMART tool (Sustainability Monitoring and Assessment Routine -Farm Tool) (Schader et al 2016), which is similar to the RISE tool. These tools assess the sustainability of agricultural production at farm level using comprehensive information on ecological, economic and social aspects collected through a questionnairebased interview with the farmer (Grenz et al 2012).…”
Section: Group 4: Consultation-based Assessment (N = 26)mentioning
confidence: 99%
“…Empirical evidence is necessary to support the statement that "diversification and economies of scope contribute significantly to more resilient pathways of development" [1]. This is essential for the formulation of precise and non-generalist policies, which is especially relevant in contexts where there may be some conflict or tradeoff between the objective of economic profitability and other (non-economic) sustainability criteria [14,20,[22][23][24]. In this setting there are few studies that have analyzed the relationship between efficiency and sustainability [15,25] and this paper aims to contribute to this area of the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Existing literature suggested that organic agriculture practices result in wide range of benefits. Studies of Lobley & Potter (2004), Zulfiqar & Thapa (2017), Berbeć et al (2018) suggested that organic agriculture improved environmental benefits, social and economic benefits, as well as increasing regional economies. • Japan organic agriculture practices is dominated by large-scale organic farmers and producers • Government has strict certification law under the Japanese Standard Law for domestic and export market • Organic retail prices are higher than conventional product by 15-20 percent • Japan's organic retail prices were competitive with China, United…”
Section: Historymentioning
confidence: 99%